Does taking a short break from social media have a positive effect on well-being? Evidence from three preregistered field experiments - Przybylski, AK; Nguyen, T-vT; Law, W; Weinstein, N (Springer, 2021)
Concerns about the consequences of social media use on well-being has led to the practice of taking a brief hiatus from social media platforms, a practice known as “digital detoxing.” These brief “digital detoxes” are becoming increasingly popular in the hope that the newly found time, previously spent on social media, would be used for other, theoretically more rewarding, activities. In this paper, we test this proposition. Participants in three preregistered field experiments (ntot = 600) were randomly assigned to receiving each of two conditions on each of two different days: a normal-use day or an abstinence day. Outcomes (social relatedness, positive and negative affect, day satisfaction) were measured on each of the two evenings of the study. Results did not show that abstaining from social media has positive effects on daily well-being (in terms of social relatedness, positive and negative affect, day satisfaction) as suggested by the extant literature. Participants reported similar well-being on days when they used social media and days when they did not. Evidence indicated that abstinence from social media had no measurable positive effect on well-being, and some models showed significant deficits in social relatedness and satisfaction with one’s day. We discuss implications of the study of social media hiatus and the value of programmatic research grounded in preregistered experimental designs.